Molecular epidemiology of influenza, respiratory syncytial virus, SARS-CoV-2, other respiratory viruses and bacteria among children 0–2-year-olds in West Bengal: a one-year influenza-like illness surveillance study (2022–2023) - Khan, Tila; Halder, Sayantan; Das, Ranjan Saurav; Jaiswal, Abhishek; Leo, Pearl Helena Scott; Mahato, Arabinda; Ghosh, Tarapada; Satpathi, Parthasarathi; Bhattacharya, Sangeeta Das (Frontiers in Epidemiology, 2025)
BackgroundLower respiratory infections are the leading cause of paediatric morbidity and mortality. This study documents the incidence and etiology of influenza-like illness (ILI) among young children in rural eastern India.MethodsWe conducted a surveillance of ILI in children visiting paediatric clinics of two hospitals in District West Midnapore, West Bengal from April 1, 2022 to March 31, 2023. Nasopharyngeal swabs were collected from children 0–2 years of age with ILI and tested for influenza, respiratory syncytial virus (RSV), and SARS-CoV-2; a representative set for the respiratory panel.ResultsOf 9,923 outpatient children 0-14 years of age screened, 1,001 had ILI, of which 439 (44%) were in 0–2-year-olds. The ILI incidence was 439/4,310 [10.2% (95% CI: 9.29–11.1)] in the 0-2-year-olds, 288/2,473 [11.6% (10.4–12.9)] in >2-5-year-olds, and, 274/3,140 [8.7% (7.7–9.7)] in >5-14-year-olds. Of 390 enrolled children (median age: 12 months), viruses were identified in 23.3%, occurring singly (15%) or with other viruses (1.3%). RSV was the most common virus (12.6%), followed by influenza (6.6%) and SARS-CoV-2 (0.77%). Influenza subtypes included IA/H3 (50%), IA/H1N1pdm2009 (34.6%) and IB (15.4%). IA/H1N1pdm09 predominated during the 2022 monsoon, RSV during 2022 autumn and A/H3 and B during 2023 winters. Cough and difficulty breathing were associated with RSV. The major bacteria detected were Streptococcus pneumoniae (55.5%), Haemophilus influenzae (29%) and Moraxella catarrhalis (3.7%). Other viruses were parainfluenza virus 3 (4.4%), bocavirus (3.7%) and adenovirus (3%). Viral-bacterial co-detections were frequent (20%). Seventeen children required hospitalization, with difficulty breathing increasing hospitalization risk (OR = 4.47, 95% CI: 1.67–12). Children with RSV had increased odds of hospitalization (OR = 3.11, 95% CI: 1–9.26).ConclusionsThe majority of ILI was observed in children aged 0-2 years, with RSV and influenza as major viral causes associated with ILI. RSV increased the risk of hospitalization. These findings contribute to building the evidence base for maternal RSV immunization policy in India.